The mechanism of rate-limiting motions in enzyme function - Watt, Eric D. (National Academy of Sciences, 2007)
The ability to use conformational flexibility is a hallmark of enzyme function. Here we show that protein motions and catalytic activity in a RNase are coupled and display identical solvent isotope effects. Solution NMR relaxation experiments identify a cluster of residues, some distant from the active site, that are integral to this motion. These studies implicate a single residue, histidine-48, as the key modulator in coupling protein motion with enzyme function. Mutation of H48 to alanine results in loss of protein motion in the isotope-sensitive region of the enzyme. In addition, k(cat) decreases for this mutant and the kinetic solvent isotope effect on k(cat), which was 2.0 in WT, is near unity in H48A. Despite being located 18 Å from the enzyme active site, H48 is essential in coordinating the motions involved in the rate-limiting enzymatic step. These studies have identified, of ≈160 potential exchangeable protons, a single site that is integral in the rate-limiting step in RNase A enzyme function.